Blender 2.6 Cycles : materials and textures cookbook - Valenza, Enrico (Open source : community experience distilled., 2013)
Written in a friendly, practical style this Cookbook deep-dives into a wide-array of techniques used to create realistic materials and textures. This book is perfect for you if you have used Blender before but are new to the impressive Cycles renderer. You should have some knowledge of the Blender interface, though this is not a strict requirement. If you want to create realistic, stunning materials and textures using Cycles, then this book is for you!